Inquiries into the subcellular localization of the glucocorticoid receptor. - Laquian, Ian R. (University of Ottawa (Canada), 2000)
In the absence of hormone, the glucocorticoid receptor (GR) resides in the cytoplasm existing in an inactive form complexed to heat shock proteins and immunophilins. Upon ligand addition, GR dissociates from the protein complex and transforms into an active free form that rapidly and completely translocates to the nucleus to regulate transcription of specific genes. Upon ligand withdrawal, GR is re-packaged into its multiprotein heterocomplex and is slowly redistributed to the cytoplasm. In this study an indirect immunofluorescence assay was employed to characterize the subcellular localization of a series of GR mutants effectively truncating, deleting or mutating specific regions of the receptor N-terminus. In the first part of my study, I delimited a specific region of GR (amino acids 100--200 of the N-terminus) necessary for both its initial cytoplasmic localization prior to ligand addition and return to the cytoplasm upon subsequent hormone withdrawal. Nuclear import of liganded GR is mediated through a well characterized sequence called NL1, which is adjacent to the receptor DNA binding domain and a second uncharacterized motif NL2, located in the ligand binding domain. Not much has been known about the NL2 mediated nuclear import of GR. The second part of my study was devoted to further characterizing the kinetics of an NL1 deficient GR mutant. (Abstract shortened by UMI.)
Keywords: Biology, Cell.